Konversation und Geselligkeit Praxis französischer Salonkultur im Spannungsfeld von Idealität und Realität - Schulz, Karin (Lettre, 2018)
Based on the field of experience of ideality and reality, Karin Schulz develops a history of behavior diagnostics concerning French parlor conversation.